76.5k views
1 vote
Please help me with this problem​

Please help me with this problem​-example-1
User Natale
by
5.9k points

1 Answer

7 votes

y=x^2 + x - 2

x + y = 1

Replace y in the second equation:

x + x^2 + x -2 = 1

Simplify:

x^2 + 2x -2 = 1

Subtract 1 from both sides:

x^2 + 2x -3 = 0

Factor:

(x-1) (x+3) = 0

Solve for both x's:

x = 1 and x = -3

Now replace x in the second equation and solve for y using both x values:

1 + y = 1, y = 0

-3 + y = 1, y = 4

Now you have (1,0) and (-3,4) as solutions for (x,y)

XY = x times y:

1 x 0 = 0

-3 x 4 = -12

The answer would be -12

User Gheorghe Graur
by
4.9k points